Priorities for Research on Gender Equality, Climate Change, and Agriculture in the MENA Region: A Policy Brief - Baruah, Bipasha; Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2023)
The Middle East and North Africa (MENA) region is extremely vulnerable to climate change and is also the most gender unequal region in the world. According to the Global Gender Gap report, the gender gap is highest in the MENA region (60.9 percent progress toward parity), and “at the current relative pace, it would take an estimated 142.4 years to close” (World Economic Forum, 2021: 26). Agriculture in the MENA region is becoming increasingly feminized, with women representing more than 50 percent of agricultural workers in some countries (Abdelali-Martini and de Pryck 2015; Najjar et al. 2018). Reducing gender inequality has been identified as an important response area requiring strengthening to enable the MENA region to adapt and build resilience toward climate change. Since women are participating out of choice and necessity in such large numbers in the agricultural workforce of the MENA region, they must be enabled and empowered to serve as active agents in climate change mitigation, adaptation, and resilience.